2018
DOI: 10.1111/echo.14125
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular resistance versus pulmonary artery pressure for predicting right ventricular remodeling and functional tricuspid regurgitation

Abstract: Noninvasive PVR was superior to PASP for predicting RV systolic dysfunction, but both were similarly associated with RV dilatation or FTR grade. PASP and PVR complement each other to define the echocardiographic findings and clinical status of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They were thorough explorations with special attention paid to the right heart chambers and pulmonary haemodynamics, with the aim of providing insights into right heart afterload adaptation. The study protocol was designed to recruit cases with complete data, no right heart abnormalities due to primary causes and avoiding cases with normal RV, strictly normal pulmonary artery systolic pressure (PASP), and absent or physiological tricuspid regurgitation [13]. Therefore, inclusion criteria were the presence of FTR with at least one of the following conditions: PASP 35 mmHg, or any degree of RV dilatation or RV dysfunction.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…They were thorough explorations with special attention paid to the right heart chambers and pulmonary haemodynamics, with the aim of providing insights into right heart afterload adaptation. The study protocol was designed to recruit cases with complete data, no right heart abnormalities due to primary causes and avoiding cases with normal RV, strictly normal pulmonary artery systolic pressure (PASP), and absent or physiological tricuspid regurgitation [13]. Therefore, inclusion criteria were the presence of FTR with at least one of the following conditions: PASP 35 mmHg, or any degree of RV dilatation or RV dysfunction.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…PVR measurements are established in the context of pulmonary hypertension [15], and studies have shown that high PVR is associated with unfavorable right ventricular remodeling and outcome in patients with tricuspid valve regurgitation [16,17]. As a marker of right heart function and congestion [18], PVR has been used as an endpoint in numerous clinical trials [19,20].…”
Section: Introductionmentioning
confidence: 99%